The Application of an Evidence-Based Clinical Nursing Path for Improving the Preoperative and Postoperative Quality of Care of Pediatric Retroperitoneal Neuroblastoma Patients: A Randomized Controlled Trial at a Tertiary Medical Institution. Issue 4 (July 2017) - Liu, Yang; Mo, Lin; Tang, Yan; Wang, Qiuhong; Huang, Xiaoyan
Abstract : Background: A clinical nursing path (CNP) that encourages patients and their families to become actively involved in healthcare decision-making processes may improve outcomes of pediatric retroperitoneal neuroblastoma (NB) patients. Objective: The aim of this study was to evaluate the utility and value of an evidence-based CNP provided to pediatric retroperitoneal NB patients undergoing resection surgery. Methods: One hundred twenty NB cases were assigned to a control group or a CNP group. The control group was provided with standard nursing care. The CNP group was provided with nursing care in accordance with an evidence-based CNP. The utility and value of the CNP were compared with standard nursing care. Outcome measures included rates of postoperative complications, lengths of hospital stay, and cost of hospitalization, as well as preoperative and postoperative quality of care and patient satisfaction with care. Results: The rates of postoperative complications, length of preoperative hospitalization, total length of hospital stay, and costs of hospitalization were significantly lower for patients receiving the CNP compared with the control group. Preoperative and postoperative quality of care and patient satisfaction with care were significantly higher in patients receiving the CNP compared with the control group. Conclusion: Adoption of a CNP for preoperative and postoperative care of pediatric retroperitoneal NB patients undergoing resection surgery improves clinical outcomes and patient satisfaction with care. Implications for Practice: A CNP can increase families' participation in a patient's recovery process, enhance nurses' understanding of the services they are providing, and improve the quality of healthcare received by patients.